Using Implementation Science Strategies to Embed Geriatric and Dementia Best Practices in Acute Care. - Nicolai, Karen; Hebert, Catherine A.; Turner, Mary Beth; Trinity, Christen; Sheppard, Jennifer; Moore, Heather (Journal of Nursing Care Quality)
Background: Hospitalizations are challenging for older adults and people living with dementia due to geriatric syndromes and behavioral disturbances. Person-centered care (PCC) is a proven strategy to improve outcomes. Problem: We experienced an increase in behavioral disturbances and long stays of Veterans with dementia in an acute care setting. Approach: We used the Consolidated Framework for Implementation Research and Expert Recommendations for Implementing Changes to implement a Geriatric-Cognitive Impairment Protocol to promote PCC and geriatric best practices. Results: Through identification of barriers and facilitators, PCC interventions were enacted, behavioral disturbances declined, and nurses reported a more person-centered environment and improved access to tools to provide evidence-based care. Conclusion: Implementation science strategies can facilitate PCC and geriatric best practices through a modifiable nursing protocol.